Returns to Education in the Russian Federation : Some New Estimates - Melianova, Ekaterina; Parandekar, Suhas D.; Patrinos, Harry Anthony; Volgin, Artem (World Bank, Washington, DC, 2020)
This paper presents new estimates of the returns to education in the Russian Federation using data from 1994 to 2018. Although the returns to schooling increased for a time, they are now much lower than the global average. Private returns to education are three times greater for higher education compared with vocational education, and the returns to education for females are higher than for males. Returns for females show an inverse U-shaped curve over the past two decades. Female education is a policy priority and there is a need to investigate the labor market relevance of vocational education. Higher education may have reached an expansion limit, and it may be necessary to investigate options for increasing the productivity of schooling.